2018
DOI: 10.1177/0890334418767382
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Twins: Factors Related to Weaning

Abstract: We have identified the factors associated with weaning in twin infants during the first 180 days of life. This knowledge can help improve strategies to increase breastfeeding rates in twins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
1
16
1
2
Order By: Relevance
“…Also, because breastfeeding duration with a first child is a strong predictor of breastfeeding duration with subsequent children [26], providing adequate breastfeeding support to first time mothers can be beneficial beyond that pregnancy. In contrast to other studies [27,28] we found that returning to work was not associated with participants achieving their individual goals. In this population, with high rates of maternal employment and only 10 weeks of mandated maternity leave, returning to work has been shown to be strongly associated with overall breastfeeding duration [22].…”
Section: Discussioncontrasting
confidence: 99%
“…Also, because breastfeeding duration with a first child is a strong predictor of breastfeeding duration with subsequent children [26], providing adequate breastfeeding support to first time mothers can be beneficial beyond that pregnancy. In contrast to other studies [27,28] we found that returning to work was not associated with participants achieving their individual goals. In this population, with high rates of maternal employment and only 10 weeks of mandated maternity leave, returning to work has been shown to be strongly associated with overall breastfeeding duration [22].…”
Section: Discussioncontrasting
confidence: 99%
“…One proposed explanation for the association of duration of breastfeeding and a lower education is that high self-esteem and breastfeeding are highly connected, so a lower education could mean that the person has less status, less control, and less power, which in turn may produce stress and lower self-esteem [ 24 , 25 , 26 , 27 ].…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…The Swedish study [ 19 ] indicated that term infants had longer breastfeeding duration if the mother was multiparous, in agreement with other studies on the impact of parity on breastfeeding duration [ 22 , 33 ]. However, there is an opposite outcome [ 23 , 26 ] if the infants are born preterm; then, being multiparous may not be as beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…In this sample however, even among participants who achieved their planned duration of breastfeeding, only 36% exclusively breastfed while in the hospital. Unfortunately, in-hospital formula supplementation of healthy breastfeeding infants is all too common [26,27] and rarely medically indicated [28].…”
Section: Discussionmentioning
confidence: 99%